3D Ti3C2Tx aerogels with enhanced surface area for high performance supercapacitors. Issue 44 (7th November 2018) - Wang, Xinyu; Fu, Qishan; Wen, Jing; Ma, Xinzhi; Zhu, Chuncheng; Zhang, Xitian; Qi, Dianpeng
Abstract : An ultra-light porous 3D Ti3 C2 T x aerogel electrode was prepared by freeze-drying the wet hydrogel, which has an ultrahigh rate capability and excellent cycling life. Abstract : Two-dimensional titanium carbide as a novel electrode material has been widely researched in the field of energy storage in recent years. However, the restacking of Ti3 C2 T x nanosheets is still a challenge, which largely restricts their development. Here, we employ the 3D architecture of a Ti3 C2 T x aerogel to restrict the restacking of 2D Ti3 C2 T x nanosheets. This special structure can not only effectively reduce the restacking of 2D materials, but also accelerate the transport of electrolyte ions in the electrode. The as-prepared Ti3 C2 T x aerogel possessed a large special surface area of 108 m 2 g −1 and achieved a special capacitance of 349 F g −1 which is retained even at a high scan rate of 2000 mV s −1 in the 3 M H2 SO4 electrolyte, indicating an ultrahigh rate capability. Moreover, at a higher current density of 20 A g −1, 90% of the initial capacitance is also retained after 20 000 charging–discharging cycles, revealing an excellent cycling stability. Furthermore, the mechanism of charge storage was investigated.